Implementation of Village Development Program in Saukang Village, East Sinjai District - Andi Bahrun Syam; Jamaluddin, Jamaluddin; Khair Khalis Syurkati; Hartati Malkab; Nirwana, Nirwana; Sulfiani, Sulfiani (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This research aims to evaluate the implementation of the Village Cash Labor Intensive Program (PKTD) in Saukang Village, East Sinjai District, Sinjai Regency. Saukang Village, East Sinjai District, Sinjai Regency. By using descriptive qualitative approach, this study explores communication, resources, disposition, and bureaucratic structure as the main variables that influence policy implementation. affecting policy implementation. Data was obtained through interviews, observation, and documentation. The results show that the PKTD program program has made a significant contribution to improving the welfare of community through the provision of local employment and the development of village infrastructure. However, challenges such as lack of socialization and human resources still need to be addressed to improve program effectiveness.